2012
DOI: 10.1186/1756-0500-5-508
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-10, IL-4, and IL-28B gene polymorphisms with spontaneous clearance of hepatitis C virus in a population from Rio de Janeiro

Abstract: BackgroundCytokines play an important role in the regulation of the immune response. In hepatitis C virus (HCV) infection, cytokine levels may influence the outcome of acute HCV infection. Polymorphisms in cytokine genes have been associated to different expression levels in response to infection. This study was carried out to investigate the association of several cytokine gene polymorphisms with disease outcome in HCV-infected patients.FindingsPatients with chronic or spontaneously resolved HCV infection wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…Like IL-10, the frequency of IL-4/589 gene polymorphisms is associated with various disease and disorders such as asthma and allergies [33]. Connected with viral infection, the IL-4-589/CT genotype is associated with spontaneous HCV clearance, while the CC genotype is linked with abnormal serum ALT levels in HCV-infected patients [19,34]. Additionally, gene polymorphism of IL-4-589 is differentially influenced by the presence of other viruses such as HBV and HIV [19,35].…”
Section: Discussionmentioning
confidence: 99%
“…Like IL-10, the frequency of IL-4/589 gene polymorphisms is associated with various disease and disorders such as asthma and allergies [33]. Connected with viral infection, the IL-4-589/CT genotype is associated with spontaneous HCV clearance, while the CC genotype is linked with abnormal serum ALT levels in HCV-infected patients [19,34]. Additionally, gene polymorphism of IL-4-589 is differentially influenced by the presence of other viruses such as HBV and HIV [19,35].…”
Section: Discussionmentioning
confidence: 99%
“…The association of this polymorphism with clearance has been reported in uremic patients (33). According to these reports, we can conclude that in some regions and racial groups including Iran and China, polymorphism at rs8099917T/G was not associated with spontaneous HCV infection clearance, but in other areas such as the United States, Europe (13), Brazil (17), and Morocco (34) this polymorphism affects HCV infection outcome. An association between this polymorphism and response to therapy in patients infected with HCV was reported in some studies (11,35).…”
Section: Discussionmentioning
confidence: 94%
“…Genetic variation in the IL28B/IFN-λ3 gene, the rs12979860 C, and the rs8099917 T allele has been shown to strongly predict viral clearance (12,13). Spontaneous clearance of HCV infection has also been reported to be associated with HLA class I and II (14,15), IL-10 (16), IL-4 (17), IFN-γ (18), and PD-1 (17). To the best of our knowledge, few studies have been conducted on the effects of these polymorphisms on spontaneous clearance of HCV infection in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Around 3-4 million persons are infected each year and more than 350,000 people die every year from hepatitis C-related liver diseases (4)(5)(6). Amongst different groups of the patients with acute HCV infection, only 15-30% could spontaneous clear the virus while the other patients have potential for promoting severe progressive liver damage (7,8). Based on the literature reports, about 70-85% of HCV infected patients develop to the chronic stage, and in 20-30% of them it leads to liver cirrhosis associated with hepatocellular carcinoma (HCC) with 1-5% death rate caused by liver cancer (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst different groups of the patients with acute HCV infection, only 15-30% could spontaneous clear the virus while the other patients have potential for promoting severe progressive liver damage (7,8). Based on the literature reports, about 70-85% of HCV infected patients develop to the chronic stage, and in 20-30% of them it leads to liver cirrhosis associated with hepatocellular carcinoma (HCC) with 1-5% death rate caused by liver cancer (8,9). Considering that several epidemiological studies were conducted in different societies, up to 80% of HCC cases were reported in East Asia and Sub Saharan Africa while only 13% occurred in America (10).…”
Section: Introductionmentioning
confidence: 99%